How EU Member States Represent the Common Purpose of Migration Management - Meyer, Sebastian, (International Law E-Books Online, Collection 2025., 2025)
Since the 'refugee crisis' in 2015, EU Member States have claimed to represent or act on behalf of the Union when regulating migration. Some measures were outside or at the margins of the EU legal order. How can Member States reconcile their double bind as members of the Union and as sovereign nation states? Enriching legal doctrine with constitutional theories, this book argues that EU law is still able to uphold the rule of law, in line with its foundational promise, while also empowering the Member States to govern migration in the common European interest. See Less